Napoleon III and the Second Empire - Price, Roger (Roger David), 1944- (Lancaster pamphlets., 1997)
Roger D. Price considers the mid-century crisis which provided Louis-Napolean Bonaparte (Napolean III) with the opportunity to gain elective office as President. The text provides: a historiographical review of the ruler and his regime; details of changing historical attitudes to the period; a survey of Napolean III's economic, social and political impact; and an outline of his achievements.